Employability Is a Journey: Conceptualising Processual Employability as a Career Identity Emergence Process - Huaiyuan Zhang; Xiaojun Zhang; Gayle Brewer (MDPI AG, 2023)
This paper aims to conceptualise processual employability with identity theory to reflect the amorphous and developmental nature of employability. Through literature review, we propose a model demonstrating how the career identity emergence process is linked with processual employability behaviour through four stages of identity change: Identity Enactment, Identity Validation, Identity Construction, and Identity Exploration. Each stage is driven by the tension between the individual's current career identity and the experienced social interactions with a changing Individual-World of Work Interface, which eventually constitutes an iterative process of employability suitable for the individual career context. It thus clarifies how the pursuit of an achieved career identity drives processual employability in a fast-changing social context and provides a holistic view of employability as a journey of identity changes. This review responds to the call for integrating developmental and sustainable views into employability and also enriches identity-based employability theories.